The Mediating Effect of Bicultural Self-Efficacy on Acculturation and Career Decision-Making Self-Efficacy for International Students in South Korea - Jin, Yuan Ying; Ahn, Sungsik; Lee, Sang Min (Frontiers in Psychology, 2022)
The population of international students in South Korea is growing. During the career development phase, international students face unique challenges related to their bicultural identity and acculturation experiences. The present study examined the role of bicultural self-efficacy on mediating the relationship between acculturation and career decision-making self-efficacy for international students in South Korea. Responses from 120 international students in South Korea were analyzed using structural equation modeling. The results showed that bicultural self-efficacy fully mediated the relationship between acculturation to mainstream culture and career decision-making self-efficacy but did not mediate the relationship between acculturation to heritage culture and career decision-making self-efficacy. The implications for effective educational intervention for international college students’ career development were discussed based on the results.